Formation of nuclear splicing factor compartments is independent of lamins A/C - Vecerová, Jaromíra; Koberna, Karel; Malínsky, Jan; Soutoglou, Evi; Sullivan, Teresa; Stewart, Colin L; Raska, Ivan; Misteli, Tom (Molecular biology of the cell, 2004)
Nuclear lamins are major architectural elements of the mammalian cell nucleus, and they have been implicated in the functional organization of the nuclear interior, possibly by providing structural support for nuclear compartments. Colocalization studies have suggested a structural role for lamins in the formation and maintenance of pre-mRNA splicing factor compartments. Here, we have directly tested this hypothesis by analysis of embryonic fibroblasts from knock-out mice lacking A- and C-type lamins. We show that the morphology and cellular properties of splicing factor compartments are independent of A- and C-type lamins. Genetic loss of lamins A/C has no effect on the cellular distribution of several pre-mRNA splicing factors and does not affect the compartment morphology as examined by light and electron microscopy. The association of splicing factors with the nuclear matrix fraction persists in the absence of lamins A/C. Live cell microscopy demonstrates that the intranuclear positional stability of splicing factor compartments is maintained and that the exchange dynamics of SF2/ASF between the compartments and the nucleoplasm is not affected by loss of lamin A/C. Our results demonstrate that formation and maintenance of intranuclear splicing factor compartments is independent of lamins A/C, and they argue against an essential structural role of lamins A/C in splicing factor compartment morphology.
Keywords: Microscopy, Fluorescence; proteiny vázající RNA; sestřih RNA; messenger RNA; Cell Nucleus; Microscopy, Electron; Microscopy, Confocal; laminy; fluorescenční mikroskopie; konfokální mikroskopie; buněčné jádro; zvířata; myši; časové faktory; Mice; myši knockoutované; RNA, Messenger; fluorescenční protilátková technika nepřímá; Lamin Type A; Lamins; Mice, Knockout; Cytoplasm; RNA Splicing; cytoplazma; fibroblasty; Fluorescent Antibody Technique, Indirect; elektronová mikroskopie; Animals; lamin typ A; RNA-Binding Proteins; Time Factors; Fibroblasts